Nemesis the last days of the American Republic - Johnson, Chalmers A (Henry Holt, 2008)
Prologue: The blowback trilogy -- Militarism and the breakdown of constitutional government -- Comparative imperial pathologies: Rome, Britain, and America -- Central Intelligence Agency: The president's private army -- U.S. military bases in other people's countries -- How American imperialism actually works: The SOFA in Japan -- Space: The ultimate imperialist project -- The crisis of the American Republic.